Serum aspirin esterase activity in cord blood and in adults - Gugliucci, Alejandro; Kimura, Satoshi; Menini, Teresita; Hermo, Ricardo; Numaguchi, Masahide (Journal of Pediatric Biochemistry, 2010)
There is scarce information about altered aspirin – esterase (AE) activities in various physiological and pathological states, as well as the putative agents modulating this activity. Since there are no data on AE levels in cord blood, we set up this study to measure its activity in neonates' cord blood and in adults, using an optimized technique developed in our laboratory. We performed a case-control study with 28 newborns, and control adult subjects were selected from a healthy population of hospital workers. Aspirin esterase activity in cord blood was 60 ± 12 nmol/mL/min vs 87 ± 12 nmol/mL/min in adults, p < 0.00001. No correlation of AE activity and HDL cholesterol, HDL/LDL cholesterol or paraoxonase 1 was found. Aspirin esterase correlated significantly with serum cholinesterase: r = 0.86 p < 0.0001, which was also 30% ower in cord blood than in adults. We show here, for the first time, that cord blood serum has a significant aspirin esterase activity, even though is its 40% lower than that found in adults. Our data provide baseline information for future studies on the physiology of aspirin esterase in children and the factors that modulate its activity to reach adult levels.
Keywords: Fetal circulation; neonate; acetylsalicylic acid; serum esterase